Changes in atmospheric deposition and streamwater chemistry over 25 years in undisturbed catchments in a Mediterranean mountain environment. - Avila, Anna; Rodà, Ferran (The Science of the total environment, 2012)
Surface water chemistry has changed in response to reduced atmospheric deposition of sulphur and acidity in many regions of Europe and North America. Most of these studies come from acidic or low-alkalinity surface waters under high acidic deposition. Mediterranean climates offer a different biogeochemical context, characterised by streamwaters of higher alkalinity and low acid inputs. In this paper, we use surveys of streamwater chemistry conducted in 1981-1984 and again in 2007 in the Montseny natural park (NE Spain) to test whether streamwaters of these well-buffered catchments respond to changes in atmospheric deposition, which has declined for S during the last decades in NE Spain while remaining about stable for nitrogen. The 23 sampled streams drained heathland, beech forests and evergreen oak forests in relatively undisturbed small catchments underlain by silicate bedrock. Bulk deposition of sulphate at Montseny decreased by 54% while nitrate bulk deposition increased (non-significantly) by 30% in this period. Total N deposition is estimated in the range 15-30 kg N ha(-1) y(-1) for NE Spain. This is well above threshold values (e.g. 10 kg N ha(-1) y(-1)) reported as starting nitrogen saturation symptoms in forest ecosystems in Europe. Baseflow sulphate concentrations decreased on average by 47 μeq L(-1) or 29% of early 1980s concentrations. Baseflow mean nitrate concentrations increased significantly but only from 5.5 to 8.9 μeq L(-1). Thus, despite decades of high N deposition, these ecosystems appear to be still far from N saturation. Baseflow alkalinity and base cation concentrations increased substantially, probably a combined result of decreased S deposition, enhanced silicate weathering under current higher temperatures, reduced plant cation uptake as vegetation matures, and slightly drier conditions in the survey of 2007. Overall, these well-buffered catchments have shown sizable changes in baseflow chemistry in response to changed atmospheric deposition and other environmental changes.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 22200374
Keywords: Alkalinity; Base cations; nitrogen; Quercus ilex; Streamwater chemistry; Sulphate

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Quercus and Pinus cover are determined by landscape structure and dynamics in peri-urban Mediterranean forest patches - Guirado, Maria; Pino, Joan; Rodà, Ferran; Basnou, Corina (Plant Ecology, 2007)
Successional dynamics in Mediterranean forests have been modulated by anthropogenic disturbances during thousands of years, especially in areas densely populated since ancient times. Our objective is to determine whether pine tree cover (early-successional species) and oak tree cover (late-successional species), used as a surrogate of successional stage of peri-urban fragmented forests in the Valle`s lowlands (Catalonia, NE, Spain), are primarily determined by (1) climate and topography; (2) anthropogenic disturbances; (3) patch structure; or (4) patch dynamics from 1956 to 1993. Quercus spp. and Pinus spp. tree cover were separately recorded on 252 randomly selected plots of 100 m 2 , within forest patches ranging in size from 0.25 to 218 ha. Multiple linear regressions indicated that forest patch history is the most important variable determining oak and pine tree cover: new forest patches showed higher pine and lower oak tree cover than recently split patches (i.e. those that became fragmented from large forest areas after 1956). Patches already existing as such in 1956 (pre-existent patches) showed higher pine cover than recently split patches. Oak cover increased and pine cover decreased with increasing forest connectivity of the patch. Finally, highly frequented forests were related to high cover of pines. Climatic and topographic variables were not signiﬁcant. We conclude that pine and oak cover in these peri-urban forests are mainly determined by recent patch dynamics, but also by the spatial pattern of patches. However, humaninduced disturbance can modulate this as there is some evidence for pine being associated with a high human frequentation.
Keywords: á pinus; á quercus forests; anthropogenic disturbances; anthropogenic disturbances á forest; Forest fragmentation; forests á patch structure; fragmentation á historical dynamics; historical dynamics; patch structure; pinus forests; Quercus forests

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

Effects of irrigation and fertilization on stem diameter growth in a Mediterranean holm oak forest - Mayor, Xavier; Rodà, Ferran (Forest Ecology and Management, 1994)
The effects of irrigation and fertilization on stem diameter growth are reported for holm oak (Quercus ilex L.), an evergreen tree that is a common dominant in Mediterranean forests. The experiment was conducted at Prades (northeastern Spain) in a holm oak stand with a high density of stems of resprout origin (x = 18275 stems ha−1), a widespread stand structure in the abandoned coppices that cover extensive tracts of Mediterranean mountains. Mean annual rainfall is 580 mm. Eight treatments were used in each of three blocks, resulting from the factorial combination of: (i) irrigation at rates of about 20 mm week−1 during three consecutive warm seasons; (ii) nitrogen fertilization in a single application of 250 kg N ha−1; (iii) phosphorus fertilization in a single application of 125 kg P ha−1. Stem diameters at 50 cm from the ground were measured before and 3 years after treatment application began. Stem diameter increments in control plots were very low (x ± SE 0.27 ± 0.07 mm year−1), probably as a result of the high stand density and low water availability. Stem diameter growth was positively but loosely correlated with initial stem diameter. Irrigation significantly (P < 0.01) increased mean stem diameter growth by 66%, but N and P fertilization did not. Surprisingly, there were no significant interactions between irrigation and fertilization, i.e. irrigated and fertilized trees did not grow significantly faster than irrigated-only trees. Effects of irrigation were larger on plots having lower initial basal area of holm oak. Irrigation increased stem diameter growth more in large trees than in smaller ones, thus enhancing the pre-existent inequalities in growth rates. Stem diameter growth in this high density stand is limited by water availability but has not responded to N or P additions during the first 3 years after fertilization.
Keywords: fertilization; Growth; irrigation; Quercus ilex; Stem diameter growth

Root biomass of Quercusilex in a montane Mediterranean forest - Canadell, Josep; Rodà, Ferran (Canadian Journal of Forest Research, 1991)
Biomass allocation to roots was studied in holm oak (Quercusilex L.), a dominant evergreen tree in broad-leaved sclerophyllous Mediterranean forests. The root systems of 32 single-stemmed holm oaks growing in shallow soils on largely unfissured bedrock were excavated in a mesic site and a xeric site in the Montseny Mountains (northeast Spain). Individual root:shoot biomass ratios (roots with diameter <1 cm not included) of single-stemmed trees were significantly higher in the xeric site (mean 0.45) than in the mesic site (mean 0.37), probably reflecting the lower water availability and higher light availability in the xeric site. It is concluded that single-stemmed holm oaks have higher root:shoot ratios than most temperate forest trees, particularly so when growing on a xeric site. Root:shoot ratios of single-stemmed trees were not linearly correlated with dbh. Allometric regressions of root biomass on dbh did significantly differ between sites. Roots <1 cm in diameter were sampled with soil cores in the mesic site. Holm oaks ≥5 cm dbh in a stand dominated by single-stemmed trees on the mesic site had an aboveground biomass of 160 t/ha and a belowground biomass of 63 t/ha. The belowground biomass was composed of 30 t/ha of root crowns plus roots >5 cm in diameter, 17 t/ha of roots 1–5 cm in diameter, and 16 t/ha of roots <1 cm in diameter. The xeric stand was dominated by multistemmed holm oaks with massive root crowns developed after repeated coppicing. Three multistemmed trees were excavated, yielding a mean root:shoot ratio of 1.2. Through resprouting from root crowns, managed or disturbed holm oak forests can accumulate a belowground biomass greater than that displayed aboveground: 91 t/ha (excluding roots <1 cm in diameter) and 79 t/ha, respectively, in our xeric stand.
doi: 10.1139/x91-245

Precipitation, throughfall, soil solution and streamwater chemistry in a holm-oak (Quercus ilex) forest - Rodà, Ferran; Avila, Anna; Bonilla, David; Rodà, Ferran (Journal of Hydrology, 1990)
Bulk precipitation, throughfall, soil solution at 20 and 40 cm depths, and stream water were monitored for 2–4 years in a holm-oak forest on schists in the Montseny Mountains (NE Spain). Bulk precipitation was mildly acidic, with Ca2+ and SO2−4 as dominant ions. Canopy interactions produced a throughfall less acidic than bulk precipitation and enriched in all other ions. Large amounts of K+ were leached from the canopy. Magnesium in net throughfall behaved similarly to K+, and it is concluded that leaching makes a major contribution to Mg2+ enrichment beneath the canopy. Judging from the moderate increase of Na+ and Ca2+ in throughfall, dry deposition rates for both marine and continental aerosols were low in the studied stand, probably because of its sheltered topographic position within a well-vegetated massif, coupled with moderate tree height and low canopy roughness. Soil solution in the mineral soil was less acidic than throughfall. In common with most temperate forests, SO2−4 was the dominant mobile anion in the soil water, being largely accompanied by Ca2+. Potassium and NO−3 were depleted within the soil water with respect to throughfall, probably owing to biological uptake and cation exchange, and incorporation of K+ into clay lattices. Subsurface flow dominated the hydrology of the small forested catchment studied. Stream water was basic and rich in bicarbonate. Its chemistry revealed fast rates of weathering of sodium- and magnesium-bearing silicates (mainly albite and chlorite, respectively). Soil respiration and silicate hydrolysis resulted in HCO−3 being the dominant mobile anion in stream water. Calcium to chloride ratios were similar in bulk precipitation and in stream water, indicating that Ca2+ release from weathering has been counteracted by plant uptake. Nutrient uptake by this aggrading forest strongly influences the solution dynamics of K+, NO3 and Ca2+. It is concluded that: (1) this forest does not currently receive acidic atmospheric deposition; (2) the neutralization capacity of the soil-bedrock system is quite high; (3) biotic regulation and silicate weathering are the major processes shaping the solution biogeochemistry in this Mediterranean forest ecosystem.
Keywords: Canopy; chemistry (voyant); Holm oak; Montseny mountains; Precipitation; soil solution; stream water; throughfall